THE IMPACT OF SIMULTANEOUS ELECTIONS ON BANKING PROFITABILITY: AN EMPIRICAL STUDY IN THE ASEAN BIG FOUR STOCK MARKET - Irada Sinta; Rico Nur Ilham; Reza Juanda; Muttaqien; Cut Zira Maulida; Frengki Putra Ramansyah (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
Capital Adequacy Ratio (CAR) is a bank performance ratio used to measure the adequacy of capital owned by the bank in order to support assets that contain or generate risk. The greater the Capital Adequacy Ratio (CAR), the better the bank's ability to meet capital needs. The greater the capital owned by the bank, the bank is able to provide loans to customers in large amounts so that it has the opportunity to increase the company's profitability. Profitability assessment is a process to determine how well business activities are carried out to achieve strategic goals, eliminate waste and present timely information to carry out continuous improvement (1). This study aims to be one of the indicators of how an important event in a country, especially in the socio-political field, can affect the country's economic turnover and stock exchange. Especially for the big four ASEAN countries (Indonesia, Malaysia, Singapore and Thailand), the case of increasing stock prices in the banking sector is in the spotlight and it is necessary to conduct a scientific study on the correlation of General Election events in the big four ASEAN countries with the increase in their country's stock market. This type of research is associative research that aims to determine the relationship between two or more variables, namely researching the influence of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR) and Operational Costs on Operational Income (BOPO) which are related to the Profitability of banking sector companies during the general election period in the big four ASEAN countries. This study will use ratio analysis to determine the performance of a bank and its health.